PENGARUH SISTEM INFORMASI AKUNTANSI MANAJEMEN, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA MANAJERIAL - Lastri Delina; Fitrawati Ilyas (JURNAL FAIRNESS, 2022)
This study aims to see the effect of management accounting information systems, work motivation, and job satisfaction on the managerial performance of managers and supervisors who work at hotel service companies in the city of Bengkulu. This study uses a quantitative approach. Respondents in this study are managers and supervisors who work in five-star hotels in Bengkulu. The sample selection in this study using purposive sampling. Sources of data in this study using primary data with a questionnaire. Data analysis using multiple linear regression analysis using the SPSS program.The results of this study indicate that there is a positive effect of management accounting information systems, work motivation, and job satisfaction on managerial performance, which means that the better the application of management accounting information systems, providing work motivation, and job satisfaction can improve managerial performance.Theoretically, the results of this study support the contingency theory which states that in carrying out their duties, managers need conformity to be able to implement a particular strategy. Contingency theory is a theory that is used as an analysis tool for forms and systems of management accounting, work motivation, and job satisfaction that are useful for providing information to companies, one of which is information to be able to face competition.The limitation in this study is the reduction in the sample because most of the hotel service companies in the capital city are temporarily closed, thus narrowing the results of this study to the number of samples that do not include all hotels in Bengkulu City.